Implementasi Virtual Tour JTE UNRI Menggunakan Kombinasi Foto Panorama Dan Rekayasa 3D - Edi Susilo; Rahmat Rizal Andhi; Febrizal Ujang; Anhar Anhar (Fakultas Teknik Universitas Hamzanwadi, 2023)
Media information has a very important role in efforts to attract prospective students to join. A website needs to be improved in the era of large technological developments. One of the new information media that utilizes the latest technology is a virtual tour. If you look at some of the previous ones, making a virtual tour can be made using panoramic photos made with image stitching techniques from many photos and can also use 3-dimensional engineering results. Both ways have their advantages and disadvantages. In this study, we will combine panoramic photos and 3D engineering to create a virtual tour of the Department of Electrical Engineering, Riau University. Virtual tour created using an equirectangular image base. There are 10 locations included in the virtual tour which four of them use panoramic photos and the remaining six places use 3D engineering. Four panoramic photos and six 3D-engineered equirectangular shapes are combined into one virtual tour. To validate the results of combining panoramic photos and 3D engineering into a virtual tour, user experience testing was conducted using a user experience questionnaire. User experience questionnaire was distributed to 30 respondents. As a result, four scales are in the excellent category: attractiveness, dependability, stimulation, and novelty. Then two scales are included in the good category, namely perspicuity and efficiency, which get a value of 1.78. From the user experience perspective, virtual tours resulting from a combination of panoramic photos and 3D engineering in general can be considered very good. Then this combination of panoramic photos and 3D engineering can be used as a solution for virtual tour documentation if several locations are inadequate to document